Internalisasi Moderasi Beragama dalam Kurikulum Pesantren - Samsul Arifin (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Indonesia's diversity is both a wealth and a blessing for the Indonesian people. This diversity can be seen from the diversity of religions adhered to by its inhabitants. One of the religions officially published by the Government of the Republic of Indonesia is Islam. Religion becomes a very important thing in human life, especially in this industrial era religion becomes a vital necessity. Along with its existence, many societies are too fanatical about their own religion so that the term extremism, radicalism, hate speech (hatred of speech) appear, which results in the recurrence of relations between religious believers. Islamic boarding schools as Islamic educational institutions began to plan to issue radical (fundamental) understandings. Therefore, in forming students who are moderate towards their religion, it is necessary to include moderation in the pesantren curriculum to minimize the existence of radical ideas. How can the students be able to fortify the efforts made by the pesantren to instill the character or principles of a moderate religious way. So by internalizing religious moderation in the pesantren curriculum, it is able to answer the needs that are currently becoming problematic today as extremism and radicalism.